Energy, environmental and economic assessment of waste-derived lemon peel oil intermingled with high intense water and cetane improver. (October 2022) - Vellaiyan, Suresh; Kandasamy, Muralidharan; Subbiah, Arunkumar; Devarajan, Yuvarajan
Graphical abstract: Highlights: A novel attempt has been made to increase the water concentration in LPO using EHN. LPO dominating in all aspects compared to ND, except for NOx . 10WLPO significantly reduces the NOx with improved performance. EHN in emulsion fuel improves the engine performance and emissions. 10WLPO has low running cost compared to other test fuels. Abstract: Waste-to-energy and its utilization in the commercial field have received wider attention in recent years. Lemon peel oil (LPO), a food waste by-product is used for this study to produce bioenergy, and a novel approach has been attempted to improve energy and environmental efficiency. The LPO was blended with different percentages of water and 2-Ethylhexyl nitrate (EHN) and the energy, environmental and economic assessments were carried out. The outcomes show that LPO dominates the normal diesel in all aspects, except for NOx emission, and 10% of water in LPO (10WLPO) improves the overall performance. Meanwhile, this trend is reversed for 20% water in LPO (20WLPO) due to a longer ignition delay period and low cetane numbers. EHN plays a vital role in fuel modification and EHN blended 20WLPO significantly improves the engine characteristics, and the engine behavior is identical to 10WLPO. The cost-benefit analysis shows that 10WLPO fuel significantly reduces the running cost compared to LPO, and the cost is further reduced to 12% while the LPO is blended with EHN.